Distribution characteristics and seasonal variation of nutrients in Rushan inshore waters - Zhang Liang; Shang Jie; Zhang Naixing; Wang Lan; Zhang Haizhou (E3S Web of Conferences)
Based on the marine environmental investigation data conducted in Rushan inshore waters in February, May, August and October 2018, the distribution characteristics and seasonal variation of nutrients were analyzed, and the eutrophication status of seawater was evaluated. The results showed that the concentrations of DIN, PO4-P and SiO3-Si were in the order of spring > winter > autumn > summer, and the distribution characteristics of DIN, PO4-P and SiO3-Si in the 4 seasons were generally high in nearshore sea areas and low in offshore sea areas. The concentrations of DIN in some station exceeded the Class Ⅱ standard in the “Sea Water Quality Standard”, while the PO4-P of each station comply with the Class Ⅱ standard. In spring, one station experienced eutrophication, while in the other seasons, there was no eutrophication observed. Correlation analysis showed that there was a significant positive correlation between petroleum and PO4-P in winter, spring and autumn. A significant positive correlation between suspended matter and DIN, PO4-P in spring, and a significant positive correlation between petroleum and DIN in autumn.